Elements of emotional and spiritual intelligence in Mohammad Natsir’s approach of da’wah - Abdullah, Fatimah (IIUM Press, 2017)
Current discourse on methodologies of da’wah has focused on various areas, such as management, leadership and media but is lacking in dimensions of emotional and spiritual intelligence in delivering the message of Islam. This lack will contribute to confusion, hatred and finally the rejection of the message itself. Therefore, there is an urgent need for a thorough understanding of emotional and spiritual intelligence in delivering the divine message of Islam locally and globally, one which is currently neglected by some Muslims. This article aims at exploring elements of emotional and spiritual intelligence in Mohammad Natsir’s (1908-1993) approach of da’wah. Through content analysis, this study found that Mohammad Natsir’s magnum opus “fiqhud da’wah”, exhibits several core elements of emotional and spiritual intelligence, which contribute to the sustainability of his da’wah. This is reflected through his discussion on ethics (akhlÉq) characterized by the concept of emotional bridging, Íikmah and purification of the soul.